YOUTH FARMERS PREFERENCE TOWARDS URBAN FARMING IN TAROGONG KIDUL SUB-DISTRIC GARUT REGENCY: PREFERENSI PEMUDA TANI TERHADAP PERTANIAN PERKOTAAN (URBAN FARMING) DI KECAMATAN TAROGONG KIDUL KABUPATEN GARUT - Dea Widyaningsih; Ait Maryani; Achmad Musyadar (Jurnal Penyuluhan Pertanian, 2022)
Tarogong Kidul District is included in the Regency Strategic Area (KSK) as an urban area. The preference of youth farmers to urban farming is very important in the implementation of urban farming activities in the District of Tarogong Kidul, Garut Regency. This study aims to analyze the level of youth farmers preferences, the factors that influence youth farmers preferences, and formulate strategies to increase youth farmers preferences towards urban farming. This study was carried out in Sukakarya Village, Sukagalih Village, and Jayaraga Village, Tarogong Kidul District, Garut Regency. The research sample consisted of 40 youth farmers aged between 15 - 35 years who were part of the farmer youth group, agricultural families, and farm laborers. The sampling technique uses purposive sampling and Slovin. Primary data collection using a questionnaire instrument. Data were processed using descriptive analysis techniques, multiple linear regression analysis, and Kendall's W concordance analysis. The results of the study showed that the preferences of young farmers reached 65% to choose / preference/like towards urban farming. Factors that influence the preferences of youth farmers to urban farming are the type of location and market orientation of urban farming. The strategy to increase the preference of youth farmers to urban agriculture can be done by introducing location-specific urban farming technology and utilizing idle land into productive land using targeted methods through extension activities.